2010
DOI: 10.1007/s10826-010-9438-8
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Independent Reports of Maternal Parenting Stress and Children’s Internalizing Symptomatology

Abstract: Although considerable research has investigated parenting stress and children's externalizing behavior problems, comparatively less has considered parenting stress in relation to children's internalizing difficulties. Even less research on parenting stress has incorporated children's report of their internalizing symptoms or the potential mediating role of children's attributional style. The current study hypothesized that children's independent reports of internalizing symptoms would be associated with mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 43 publications
4
62
0
1
Order By: Relevance
“…This result, which confirms the literature (Camisasca et al 2010;Costa et al 2006;Rodriguez 2011), could be explained by considering that maternal stress could be mainly characterized by feelings of worry, preoccupation, and frustration. According to Costa et al (2006), the types of feelings and beliefs included in the component parent-child dysfunctional interaction (e.g., feelings of disappointment in their children and beliefs that their children do not meet their expectations) could promote a negative emotional climate, a reduced maternal responsiveness, and a poor parent-child bond that may prompt anxious and depressed behaviors in children.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result, which confirms the literature (Camisasca et al 2010;Costa et al 2006;Rodriguez 2011), could be explained by considering that maternal stress could be mainly characterized by feelings of worry, preoccupation, and frustration. According to Costa et al (2006), the types of feelings and beliefs included in the component parent-child dysfunctional interaction (e.g., feelings of disappointment in their children and beliefs that their children do not meet their expectations) could promote a negative emotional climate, a reduced maternal responsiveness, and a poor parent-child bond that may prompt anxious and depressed behaviors in children.…”
Section: Discussionsupporting
confidence: 90%
“…In literature, although the idea that parenting stress has adverse effects on children's well-being is well established (Costa et al 2006;Crnic and Low 2002;Ö stberg and Hagekull 2013;Rodriguez 2011), more recently, some scholars have distanced themselves from the prominent hypotheses that parenting behaviors explain the relationship between parenting stress and children's emotional and behavioral difficulties (Abidin 1992). These authors assign a particularly meaningful role to parenting stress since they detect how it impacts directly the children's adjustment (Anthony et al 2005;Camisasca et al 2010;Crnic et al 2005) without the mediation of parenting behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, research suggests that parenting stress is associated with both child externalizing (Dubois-Comtois et al 2013) and internalizing behavior problems (Rodriguez 2011). However, it is unknown whether parenting stress is differentially associated with externalizing or internalizing behavior problems.…”
Section: The Impact Of Parenting Stress On Child Behaviormentioning
confidence: 99%
“…Cross-sectional findings have demonstrated strong associations between parenting stress and behavioral disorders in early childhood (Anthony et al 2005) and adolescence (Anderson 2008), and longitudinal work has shown child behavioral disorders predict higher subsequent levels of parenting stress over time (Williford et al 2007). In addition to child behavioral disorders, levels of parenting stress have also been shown to be related to child mood disorders, such as depression and anxiety (Rodriguez 2011). However, there are considerably fewer studies examining the relation between parenting stress and child mood disorders, than child behavioral disorders (Östberg and Hagekull 2013).…”
Section: Parenting Stress and Child Behavioral And Mood Disordersmentioning
confidence: 99%
“…However, maternal stress and anxiety is negatively associated with parenting skills, and with infant and child behaviour problems 22–24. Maternal anxiety is a significant predictor of child attention and aggression problems25 and maternal stress is significantly associated with anxiety and depressive symptoms in the child 26…”
Section: Introductionmentioning
confidence: 99%